Pembelajaran Group Investigation (GI) dan Pengaruhnya Terhadap Hasil Belajar Melalui Keterampilan Proses Sains (Aspek Verbal dan Menghitung) - Wahyu Wiyono; Rini Widarti; Nurul Sofiyah (Program Studi Pendidikan Matematika IKIP PGRI Jember, 2019)
This research is to know the influence of group investigation study method toward the learning result, the influence of science process skill toward learning result, and joint influence between group investigation study method and science process skill toward learning result. The problems studied in this research are: 1) is there any influence of group investigation learning method toward SD learning outcomes ?, 2) is there any influence of science process skill toward SD learning result ?, and 3) is there any interaction influence of group investigation study method and science process skill towards learning outcomes? Objectives: 1) examine the effect of group investigation learning methods on SD learning outcomes. 2) examine the influence of science process skills on student learning outcomes. 3) examine the interaction of the influence of group investigation learning methods and the skills of the science process on learning outcomes. The population of this study is the students of class V MIN Sempolan 2015/2016 academic year with the number of 32 students, the study area is determined by purposive sampling method. This research is a quantitative research with causal design. Data collection tools use questionnaires, tests and methods of documentation and interview. Valid and valid reliability tools with validity and reliability tests. The instrument analysis test uses: 1) descriptive test, 2) classical assumption test. Test the hypothesis by: 1) regression analysis, 2) F test, 3) t test, 4) test coefficient of determination (R2). The results showed that: 1) sig value. From model variable of group investigation study method toward student learning result 0.000, sig conclusion. > 0,05, mean study group investigation method have significant effect to result of student learning, 2) sig value. Of the science process skill variable is 0.000, the sig conclusion. > 0,05, this means science process skill have significant effect to student learning result, 3) result of regression analysis output obtained Fcount 50.325 with sig. 0.000, because> 0,05 then there is interaction influence of study group investigation method and skill of science process is signifikan to result of learning. Suggestions are proposed for teachers to apply learning using group investigation study methods and pay attention to the skills of the science process to achieve better learning outcomes